Factors in determining information systems development methodologies: a systematic literature review - Saeed, Yahya Ateik Al-Sagheer; Zulkifli, Zahidah; Shikh Nasir, Sumaia; Ahmed, Wani Bilal (Sohar University, 2025)
Choosing the appropriate Software Development Life Cycle (SDLC) methodology is a complex task for many firms and software engineers. The challenge arises not only from a lack of understanding of the criteria needed to select a methodology that adds value to the firm but also from a limited recognition that a methodology can be applicable across multiple life cycle models. This study aims to identify the critical factors influencing the choice of Information Systems (IS) methodologies for development projects. To address this, we conducted a systematic literature review (SLR), adapting a mapping study process from existing guidelines to categorize and structure the research evidence published in the field of IS methodologies. Our synthesis of 36 relevant papers identified four key factors influencing the selection of IS development methodologies: (1) Security, (2) Quality, (3) Communication, and (4) Test Cases. These findings provide a valuable framework for selecting appropriate IS development methodologies, focusing on factors that can serve as benchmarks for making informed choices. Furthermore, the ongoing digital transformation, accelerated by the 2020 pandemic, has underscored the urgency of integrating robust IS methodologies, particularly in the context of higher education institutions, which have swiftly shifted towards online learning and digital student services.